Hyperglycaemia accelerates local cellular inflammaging senescence and alters the periodontal tissues environment during periodontitis / Younis L.T. ... [et al.] - L.T., Younis; N.S., Razali; M.H., Zainal Abidin; M.I., Abu Hassan (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Diabetes mellitus is a group of metabolic diseases which have several aetiologies that involve millions of people around the world. Hyperglycaemia, the hallmark of diabetes mellitus, causes detrimental complications such as nephropathy, neuropathy, retinopathy, and cardiovascular disease in both Type 1 and 2 diabetic patients. Inflammaging is recently linked with the development of diabetic complications. Local cellular senescence and its senescence-associated secretory phenotype (SASP) are the main contributors to inflammaging which can be triggered and accelerated by high glucose level. Regarding the oral cavity, hyperglycaemia, provokes the severity of inflammation and destruction in the tooth supporting structures (periodontium) and increases the susceptibility to periodontitis and eventually tooth loss. This paper provides insights into the impact of hyperglycaemia in causing cellular senescence of teeth supporting tissues and escalating periodontal tissue deterioration.